Cranioplasty Training Innovation Using Design Thinking: AugmentedReality and Interchangeability-Based Mannequin Prototype - Djoko Kuswanto; Athirah Hersyadea Alifah Putri; Ellya Zulaikha; Tedy Apriawan; Yuri Pamungkas; Evi Triandini; Nadya Paramitha Jafari; Thassaporn Chusak (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
Cranioplasty, a surgical procedure to reconstruct the anatomical structure of the human skull, is commonlyperformed in Indonesia due to the malignancy of diseases, traffic accidents, and workplaceinjuries. If left untreated, this condition can lead to serious complications. Although cranioplasty isgenerally considered a relatively easy surgery, it has a fairly high postoperative complication rate ofaround 10.3%. The decreasing availability of cadavers for anatomical studies has significantly limitedtraining opportunities. Therefore, efficient and effective training tools are essential, especially whentraditional resources are insufficient to meet educational needs. Additionally, the training capabilitiesof commercially available mannequins or replicas used in medical institutions remain limited. Themain objective of this project was to develop a smart, modular cranioplasty training mannequin designedfor repeated use, incorporating Augmented Reality (AR) technology to visualize anatomicalstructures that cannot be physically replicated. Using a design thinking approach, data was collectedthrough interviews with neurosurgeons, neurosurgery residents, and cranioplasty specialists, as well asthrough a review of relevant literature. Usability testing of the developed prototype yielded promisingresults, with high ratings for ease of use (4.8), training effectiveness (4.5), anatomical realism (4.3),and material durability (4.5) on a 5-point Likert scale. These findings demonstrated strong user approvaland confirmed the model’s potential to support surgical skill development in a practical andreproducible manner. The resulting AR-integrated training mannequin offers an innovative, engaging,and durable solution to address current challenges in neurosurgical education, especially in resourceconstrainedsettings.